Development and motor control of individuals institutionalized in shelters - Silva, Cássia Kelly (2019)
Introduction: Changes in motor control are the first that may appear, compromising individual development and the learning of motor skills. Objective: Verifying and comparing development and motor control of children and teenagers institutionalized in shelters with those who live in a family environment. Methods: It has been evaluated 54 children and teenagers divided into Shelter Group (SG) and Control Group (CG). The evaluation of psychomotor development has been done by Psychomotor Battery; motor control, by the computational task Fitts Reciprocal Aiming Task v.1.0 (Horizontal). Results: Lower SG scores have been found in motor development analysis; however, both groups have been presented “good” profiles. In addition, it has been found a considerable increase in the movement from ID2 to ID4a with maintenance from ID4a to ID4b, and from ID4b to ID6. Conclusion: SG individuals presented appropriate psychomotor development according to their age with deficit in the motor control and longer movement time in relation to the CG, showing bigger difficulty in the speed.